Phase change electrolyte separator for solid-state batteries

By using phase change electrolyte separator layer and anti-dendrite layer in lithium-ion batteries, the battery short circuit problem caused by dendrite is solved, and the safety and life of the battery are improved.

CN114207900BActive Publication Date: 2025-02-25TERAWATT TECHNOLOGY INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080054030.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-29
Filing Date
2020-07-24
Publication Date
2025-02-25
Estimated Expiration
2040-07-24

AI Technical Summary

Technical Problem

Lithium-ion batteries may form dendrites during charging, causing short circuits in the diaphragm, damaging the battery and possibly overheating or ignition.

Method used

A phase transition electrolyte separator layer containing a non-reactive scaffold and liquid lithium is used. The liquid lithium is converted into a lithium gel after heating, and combined with an anti-dendrite layer to inhibit dendrite growth.

Benefits of technology

Effectively inhibit the growth of dendrites, prevent diaphragm short circuit, and improve the safety and life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114207900B_ABST
    Figure CN114207900B_ABST
Patent Text Reader

Abstract

Various arrangements of phase change electrolytes for solid state batteries (SSBs) are proposed. A phase change electrolyte separator layer may include a non-reactive scaffold having an open space. Liquid lithium converted to a lithium gel may be used, and the liquid lithium may include: a polymer additive, a cross-linker additive, a mixture of lithium salts; and a solvent. The liquid lithium with the polymer additive and the cross-linker additive may be filled into the open space within the non-reactive scaffold. When the liquid lithium is within the open space within the non-reactive scaffold, after heating, the liquid lithium may be converted into a lithium gel within the non-reactive scaffold.
Need to check novelty before this filing date? Find Prior Art

Description

Background Art

[0001] During the charging of a lithium-ion battery, lithium ions migrate from the cathode of the battery to the anode of the battery through the separator located between the cathode and the anode. Through a process called intercalation, lithium ions are embedded into the material that acts as the anode. During this charging process, lithium ions may also be plated on the surface of the anode that faces the separator. The nucleation energy associated with the anode can promote the plating of lithium ions on top of other lithium that has been plated on the anode (rather than being plated in a roughly uniform film opposite the surface of the anode). These lithium pools may form dendrites. Dendrites can be protrusions of lithium metal that extend away from the surface of the anode toward the separator. Over time (e.g., through multiple charge and discharge cycles), dendrites may grow to a certain length that the dendrite pierces the separator and directly electrically connects the cathode to the anode (i.e., short circuits). This electrical connection can cause damage to the battery and may cause serious side effects such as overheating and fire. Summary of the invention

[0002] Various embodiments related to phase change electrolytes for solid state batteries (SSBs) are described. In some embodiments, phase change electrolytes for solid state batteries (SSBs) are described. The SSB may include a phase change electrolyte separator layer, which includes a non-reactive support. The physical structure of the non-reactive support may form an open space within the non-reactive support. The phase change electrolyte separator layer may include liquid lithium, which includes a polymer additive, a cross-linker additive, a lithium salt, and a solvent that can dissolve the lithium salt. The polymer additive and the cross-linker additive may be mixed into the liquid lithium. The liquid lithium may be filled into the open space within the non-reactive support. When the liquid lithium may be within the open space within the non-reactive support, after heating, the liquid lithium is converted into lithium gel within the non-reactive support.

[0003] Embodiments of such a device may include one or more of the following features: The non-reactive support may be composed of polyethylene (PE) or polyethylene oxide (PEO). The lithium salt may be selected from the group consisting of LIFSI, LITFSI and LiPF6. The SSB may also include a first glue layer and a second glue layer. The first glue layer may contact the non-reactive support on the first side, and the second glue layer may contact the non-reactive support on the second side. The first glue layer and the second glue layer may include ceramics. The SSB may further include an anti-dendritic layer that may contact the first glue layer or the second glue layer. The polymer additive may be selected from the group consisting of P4VP and PDMEMA. The crosslinker additive may be selected from the group consisting of C12TFSA and C6TFSA.

[0004] In some embodiments, a method for making a phase change electrolyte for a solid-state battery (SSB) is described. The method may include forming a non-reactive support so that the physical structure of the non-reactive support can form an open space within the non-reactive support. The method may include forming a liquid electrolyte mixture. The liquid electrolyte mixture may include a polymer additive, a cross-linker additive, and liquid lithium. The liquid lithium may include a lithium salt and a solvent that can dissolve the lithium salt. The method may include infiltrating the liquid electrolyte mixture into the open space within the non-reactive support. The method may include: after the liquid electrolyte mixture has infiltrated into the open space within the non-reactive support, heating the liquid electrolyte mixture to convert the liquid electrolyte mixture into a gel electrolyte within the non-reactive support.

[0005] Embodiments of this method may include one or more of the following features: The method may include attaching a first glue layer to a first side of the non-reactive support before infiltrating the liquid electrolyte mixture into the open space within the non-reactive support. The method may include attaching a second glue layer to a second side of the non-reactive support opposite to the first side of the non-reactive support before infiltrating the liquid electrolyte mixture into the open space within the non-reactive support. The method may also include layering the non-reactive support to which the first glue layer and the second glue layer are attached between the cathode layer and the anti-dendrite layer. Before infiltrating the liquid electrolyte mixture into the open space within the non-reactive support, the non-reactive support to which the first glue layer and the second glue layer are attached may be layered between the cathode layer and the anti-dendrite layer. The first glue layer and the second glue layer may include ceramics. The non-reactive support may be composed of polyethylene (PE) or polyethylene oxide (PEO). The lithium salt may be selected from the group consisting of LIFSI, LITFSI and LiPF6. The polymer additive may be selected from the group consisting of P4VP and PDMEMA.

[0006] In some embodiments, a solid-state battery (SSB) is described. The SSB may include a cathode. The SSB may include an anode current collector. The SSB may include a phase change electrolyte separator layer between the cathode and the anode current collector, which may include a non-reactive support. The physical structure of the non-reactive support may form an open space within the non-reactive support. The SSB may include a phase change electrolyte separator layer between the cathode and the anode current collector, which may include liquid lithium that may be converted into a lithium gel. The liquid lithium may include a polymer additive, a cross-linker additive, a lithium salt, and a solvent that can dissolve the lithium salt. The polymer additive and the cross-linker additive may be mixed into the liquid lithium. The liquid lithium with the polymer additive and the cross-linker additive may be filled into the open space within the non-reactive support. When the liquid lithium may be within the open space within the non-reactive support, after heating, the liquid lithium may be converted into a lithium gel within the non-reactive support.

[0007] Embodiments of such a device may include one or more of the following features: A first glue layer may contact the non-reactive support on a first side, and a second glue layer may contact the non-reactive support on a second side. The SSB may further include an anti-dendrite layer that may contact the first glue layer or the second glue layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 An embodiment of a stack-up of an anode-free solid-state battery with a lithium gel separator layer and an anti-dendrite layer is shown.

[0009] Figure 2 Another embodiment of a stack-up for an anode-free solid-state battery having a lithium gel separator layer and an anti-dendrite layer is shown.

[0010] Figure 3A An example of a lithium gel separator layer formed by heating is shown.

[0011] Figure 3B An embodiment of a method for manufacturing a lithium gel separator layer is shown.

[0012] Figure 4 An embodiment of a method of making a pouch cell including an anode-free solid-state battery having a lithium gel separator layer and an anti-dendrite layer is shown.

[0013] Figure 5 An embodiment of a cylindrical battery compression system is shown.

[0014] Fig. 6A and Figure 6B An embodiment of a method for making a cylindrical anti-dendrite anode-free solid-state battery is shown.

[0015] Figure 7 An embodiment of a stack-up of an anode-free solid-state battery having a lithium gel separator layer, an anti-dendrite layer, and an interfacial bonding layer is shown.

[0016] Figure 8 An example of a stack-up of an anode-free solid-state battery is shown indicating the relative amounts of adhesion between the various layers.

[0017] Fig. 9 An example of a stack of an anode-free solid-state battery being charged is shown, where lithium is deposited on the interfacial bonding layer.

[0018] Fig.10 An embodiment of a method for making a pouch cell comprising an anode-free solid-state battery having a lithium gel separator layer, an anti-dendrite layer, and an interfacial bonding layer is shown. DETAILED DESCRIPTION

[0019] The introduction of an anti-dendrite layer in conjunction with a lithium gel separator layer can inhibit the growth of dendrites without significantly increasing the thickness of the battery cell. The anti-dendrite layer can be directly coated onto the anode current collector of an anode-free solid-state battery (SSB). In an anode-free SSB, the anode current collector (which can be a copper foil) can effectively serve as both the anode and the anode current collector. The anti-dendrite layer can reduce the nucleation energy required for lithium ions to deposit as lithium metal on the surface of the anode current collector in direct contact with the anti-dendrite layer. Unlike lithium ions, which tend to plate on top of lithium metal that has been plated onto the surface of the anode current collector (thus forming a pool that may cause dendrites), lithium may tend to be deposited in a roughly uniform film located opposite the surface of the anode current collector.

[0020] The anti-dendrite layer can be in direct contact with the lithium gel separator layer. The lithium gel separator layer can play multiple roles. First, the lithium gel separator layer can act as a solid electrolyte to facilitate the movement of lithium ions between the cathode and the anode. The lithium gel separator layer also acts as a separator to prevent direct electrical connection between the cathode and the anode. The lithium gel separator layer can also have properties that further inhibit dendrite growth.

[0021] Further details regarding these and additional embodiments are provided with reference to the accompanying drawings. Figure 1 An embodiment of a stack 100 of an anode-free solid-state battery with a lithium gel separator layer and an anti-dendrite layer is shown. The stack 100 may include a cathode current collector 110, a cathode 120, a lithium gel separator layer 130, an anti-dendrite layer 140, and an anode current collector 150.

[0022] The cathode current collector 110 may be a conductive film layered with the cathode 120. The cathode current collector 110 may be, for example, an aluminum foil. Other forms of conductive foil are also possible. The cathode 120 may be, for example, NCA (nickel cobalt alumina) or NCM (nickel manganese cobalt).

[0023] The cathode 120 may have a first surface in direct contact with the cathode current collector 110, and the opposite surface of the cathode 120 may be in direct contact with the lithium gel separator layer 130. The lithium gel separator layer 130 may act as a solid electrolyte (in gel form) to facilitate the movement of lithium ions between the cathode 120 and the anode current collector 150. The lithium gel separator layer 130 also acts as a separator to prevent direct electrical connection between the cathode 120 and the anode current collector 150. The lithium gel separator layer 130 may have properties that further inhibit dendrite growth. Initially, the lithium gel separator layer 130 may be at least partially in a liquid state. After assembly, a process may be used to convert the liquid state into a gel state. This process may involve pressurization, heating, or both. Reference Figure 3A Further details regarding the lithium gel separator layer 130 are provided.

[0024] The lithium gel separator layer 130 may have a first surface in direct contact with the cathode 120. A second surface opposite the first surface of the lithium gel separator layer 130 may be in direct contact with the anti-dendrite layer 140. The anti-dendrite layer 140 may have several key properties: First, the anti-dendrite layer 140 may reduce the nucleation energy required for lithium ions to plate lithium metal on the surface of the anode current collector 150 in direct contact with the anti-dendrite layer 140. By reducing the nucleation energy, the lithium ions may be more likely to be deposited directly on the anode current collector 150, rather than "pooling" or depositing on lithium metal that has been plated on the anode current collector 150.

[0025] The second key characteristic of the anti-dendrite layer 140 is that the amount of adhesion between the anti-dendrite layer 140 and the anode current collector 150 is less than the amount of adhesion between the anti-dendrite layer 140 and the lithium gel separator layer 130. By having less adhesion between the surface of the anti-dendrite layer 140 and the surface of the anode current collector 150, lithium is promoted to be plated between the anti-dendrite layer 140 and the anode current collector 150, rather than between the lithium gel separator layer 130 and the anti-dendrite layer 140.

[0026] The anti-dendrite layer 140 can be relatively thin. For example, the anti-dendrite layer 140 can be between 0.05 μm and 10 μm. In some embodiments, the anti-dendrite layer 140 can be deposited as a film on the surface of the anode current collector 150. The anti-dendrite layer 140 can be made of one or more of the following materials: carbon black, acetylene black, silver, zinc, gold, bismuth, tin, polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylic acid (PAA) and carboxymethyl cellulose butadiene rubber (CMC-SBR). Alloys of silver, zinc, gold, bismuth and tin can also be used to form the anti-dendrite layer 140. Although the anti-dendrite layer 140 can be formed of a single type of material, the multiple materials indicated can be used to form the anti-dendrite layer 140.

[0027] The anode current collector 150 may have a first surface in contact with the anti-dendrite layer 140. The anode current collector 150 may act as an anode and an anode current collector. In some embodiments, the anode current collector 150 is a conductive foil, such as a copper foil. In the absence of the anti-dendrite layer 140, the anode current collector 150 may exhibit a higher nucleation energy, which tends to cause lithium to gather during battery cell charging rather than being deposited as a film.

[0028] Figure 2 Another embodiment of a stack 200 of an anode-free solid-state battery having a lithium gel separator layer and an anti-dendrite layer is shown. In some embodiments, multiple sets of layers can be stacked together to increase the charge capacity of the battery cell. Figure 2 In the embodiment shown, reference is made to Figure 1The layers 110-150 are described in detail. In addition, the anti-dendrite layer 210 is stacked on the side of the anode current collector 150 opposite to the anti-dendrite layer 140. The second lithium gel separator layer 202 is in direct contact with the anti-dendrite layer 210. In addition, the cathode 230 and the cathode current collector 240 are layered on the lithium gel separator layer 220. Figure 2 Additional layers may be added in the same manner as described in detail. For example, below the cathode current collector 240 may be another cathode, followed by another lithium gel separator layer, and so on. For example, multiple groups of layers may be added to increase the charge capacity of the battery cell. Although Figure 1 A single stacked group is shown and Figure 2 A dual stack is shown, other embodiments may include more stacks, such as 16 or more. Once stacked together, the layers may be sealed as part of a pouch cell.

[0029] Figure 3A An embodiment of a lithium gel separator layer formed by heating is shown. Figure 3A Also detailed Figure 3B An embodiment of a method for making a lithium gel separator layer is shown. The lithium gel separator layer can act as a phase change electrolyte, which can be used in a solid-state battery. The lithium gel separator layer, such as the lithium gel separator layer 130, can include multiple sublayers and can be formed by heating. Pressurization can also be applied to increase the surface area of ​​the interface between the lithium gel separator layers. First, a non-reactive scaffold can be formed at frame 350. For example, the scaffold material 305 can be polyethylene (PE) or polyethylene oxide (PEO). The scaffold material 305 can be permeable so that a liquid such as an electrolyte liquid can be infiltrated, injected or otherwise introduced into the scaffold material 305. The physical structure of the scaffold material 305 can form a gap that can be filled with a liquid. For example, the scaffold material 305 can have a porosity between 10% and 90%, and a liquid can be introduced therein. The specific physical structure can be a honeycomb structure, a spider web structure, or some other pattern or randomly porous physical structure that allows the liquid to fill the empty space within the scaffold material 305. The thickness of the scaffold layer can be between 1 μm and 100 μm. In some embodiments, the scaffold layer is 15 μm thick.

[0030] At box 355, a first glue layer can be attached to the non-reactive support. At box 360, a second glue layer can be attached to the opposite side of the non-reactive support. Thus, the support material 305 can be located between the two glue layers 310. These three layers can together form a dry separator layer 300 into which an electrolyte has not yet been introduced. Each glue layer 310 can include PVDF, PI, PAA, or CMC-SBR. Such materials can be used as binders. Therefore, the glue layer 310 can be used to increase the adhesion between the support material 305, the cathode 120, and the anti-dendrite layer 140. The adhesion between the lithium gel separator layer 130 and the anti-dendrite layer 140, at least in part due to the glue layer, can be greater than the adhesion between the anti-dendrite layer 140 and the anode current collector 150.

[0031] In some embodiments, ceramics may be added to one or both glue layers to improve lithium ion transport and may help prevent dendrite formation. Such ceramics may include: MgO, PZT, BaTiO3, SBT, BFO, LATSPO, LISICON, LICGC, LAGP, LLZO, LZO, LAGTP, LiBETI, LiBOB, LiTf, LiTF, LLTO, LLZP, LTASP, and LTZP. The thickness of each glue layer 310 may be between 1 μm and 500 μm. The use of ceramics in the glue layer can reduce ionic conductivity. The use of lithium ion conductor ceramics may still reduce ionic conductivity (compared to liquids), but can ensure higher ionic conductivity compared to other ceramics. However, the advantages of ceramics in preventing short circuits and reducing overall battery failure rates may outweigh the disadvantages caused by reduced ionic conductivity.

[0032] At box 365, a liquid electrolyte mixture can be formed. The liquid electrolyte mixture can include: a lithium salt, a solvent, and an additive. The salt can be LIFSI, LITFSI, or LiPF6. The concentration of the salt can be between 1.0 mol / L and 4.0 mol / L. The lithium salt can make liquid lithium act as an electrolyte. The solvent can be: dimethyl carbonate (DMC), dimethoxyethane (DME), diethyl carbonate (DEC), dioxolane (DOL), bistrifluoroethyl ether (BTFE), ethyl methyl carbonate (EMC), or ethylene carbonate (EC). The solvent can play a role in dissolving the salt.

[0033] The additive may include a compound in the liquid lithium that, when heated, changes from a liquid to a gel. Typically, the additive includes a polymer and a crosslinker. When the additive is heated to, for example, 60°C to 150°C, the crosslinker ignites and causes further polymerization of the polymer and the solvent. Since the lithium salt is evenly distributed throughout the solvent, when the gel is formed, the lithium salt will be evenly distributed throughout the gel. One or more additives may include CsPF6, fluoroethylene carbonate (FEC), polycarbonate (PC), or LiNO3. The additive may have a concentration of 0.01-4.0 mol / L. The additive includes a polymer additive and a crosslinker additive, and the additive may be mixed into the liquid lithium before the liquid lithium permeates the entire non-reactive scaffold.

[0034] One possible combination of lithium salt and solvent may be 4M LiFSI dissolved in DME, to which the additives may be added. Table 1 indicates the combinations of polymer additives and crosslinker additives, and the relative concentrations at which the polymer additives and crosslinker additives may be used.

[0035]

[0036]

[0037] Table 1

[0038] In some embodiments, one or more additional additives may also play a role in reducing side reactions. The purpose of adding additives is to help form LiF, a solid electrolyte interphase (SEI), which can prevent various side reactions of lithium metal.

[0039] Although the lithium gel separator layer is in the form of a dry separator layer 300, the dry separator layer 300 can be laminated with other battery cell layers in place of the lithium gel separator layer 130. Once the battery cell layers are assembled and the battery cell has been inserted into a housing (e.g., a pouch), liquid electrolyte can be added, and then heat and pressure can be applied.

[0040] At box 370, the liquid electrolyte mixture can penetrate into the non-reactive support. Arrow 315 indicates that the liquid lithium penetrates into the entire support material 305 to form a liquid lithium-infiltrated support material 320. When immersed in atmospheric pressure for a period of time, such as between 6 hours and 24 hours, the liquid lithium can penetrate into the support material. This step can be performed after the dry diaphragm layer is assembled as part of the battery cell. The liquid electrolyte, which can be liquid lithium, can be composed of a material that causes the liquid lithium to at least partially solidify (e.g., solidify into a gel) after penetrating into the pores in the support material and then being heated. This arrangement allows the lithium gel diaphragm layer to be initially formed as a dry diaphragm layer, and then allows the liquid lithium to penetrate into the entire support material and transform into a gel after the battery cell is contained in a housing (e.g., a soft pack battery). In some embodiments, pressure is also applied, and the purpose of pressurization can be to increase the amount of contact at each interface within the stack.

[0041] After the liquid lithium has infiltrated the entire scaffold material 305 to form the liquid lithium infiltrated scaffold material 320, block 375 may be performed, where pressure or heat or both may be applied, as indicated by arrow 325. For example, in some embodiments, the scaffold material 305 may be first heated at room temperature at 100 N / cm 2 The pressure is applied and maintained for 60 to 120 seconds. Then the pressure can be increased at 100-500 N / cm at a temperature between 100°C–110°C. 2 The heat pressing process is performed with a pressure of 100° for a duration of between 60 and 120 seconds. The heat applied to the lithium gel membrane layer 301 can cause the liquid lithium-infiltrated support material 320 to be transformed into a quasi-solid lithium gel layer 330. In some embodiments, the pressure can promote the process or can help increase the surface area of ​​the interface between the lithium gel membrane layer and / or other layers of the battery cell. The lithium gel membrane layer 302 can then be finally formed.

[0042] To fabricate such a battery cell, various methods may be performed. Figure 4 An embodiment of a method 400 for making a pouch cell comprising an anode-free solid-state battery having a lithium gel separator layer and an anti-dendrite layer is shown. At block 405, the anti-dendrite layer may be laminated on the anode current collector. Figure 1 The anti-dendrite layer 140 is described in detail. Figure 1 The anode current collector 150 will be described in detail.

[0043] At block 410, a three-part lithium gel separator layer may be formed. Initially, the lithium gel separator layer may be in the form of a dry separator layer. That is, a liquid electrolyte, such as liquid lithium, has not yet been injected into the support layer, as shown in FIG. Figure 3ADetailed. In other embodiments, the support material at box 410 has been infiltrated with liquid. At box 415, a lithium gel separator layer in which liquid lithium may be present or has not yet been introduced can be laminated to the anti-dendrite layer. The amount of adhesion between the lithium gel separator layer and the anti-dendrite layer can be greater than the amount of adhesion between the anti-dendrite layer and the anode current collector. In some cases, after heating and pressurizing at box 430, the amount of adhesion between the lithium gel separator layer and the anti-dendrite layer can be greater than the amount of adhesion between the anti-dendrite layer and the anode current collector.

[0044] At block 420, the cathode layer can be laminated onto the lithium gel separator layer (where the gel is still in a liquid state or has not yet been introduced into the support material). At block 425, the cathode current collector layer can be laminated onto the cathode layer. In some embodiments, block 425 can be performed and then the combined cathode layer and cathode current collector layer can be laminated onto the lithium gel separator layer at block 420 (where the gel is still in a liquid state or has not yet been introduced into the support).

[0045] It should be understood that blocks 405-425 may be repeated multiple times to form multiple stacks for a solid-state battery cell. Figure 2 16 sets of layers were made in the stack described. This arrangement was such that the anode current collector and cathode current collector were in contact with the anti-dendrite layer and cathode, respectively, on opposite sides.

[0046] At box 430, one or more stacks may be packaged in a soft pack battery. At this box, the liquid lithium (or other form of liquid electrolyte), assuming it was introduced at box 410, may still be liquid. The stack may be vacuum sealed within the soft pack battery to remove excess air. The soft pack battery may be made of a flexible material, such as plastic, which allows the soft pack to expand and compress. If the liquid lithium does not penetrate the entire support layer at box 410, the liquid lithium may be introduced into the soft pack battery at box 432 while packaging is being performed (or before or after). The liquid lithium may then penetrate into the support layer of the dry diaphragm layer.

[0047] At box 435, one or more processes of heating, pressurizing, or both may be applied to the packaged soft pack battery. This process may perform multiple functions: 1) box 435 may increase the amount of physical contact between adjacent layers of the battery cell; 2) box 435 may convert the liquid lithium into lithium gel; and 3) box 435 may generate an adhesion between the anti-dendrite layer and the lithium gel layer that is greater than the adhesion between the anti-dendrite layer and the anode current collector. For example, in some embodiments, the anode current collector may first be heated at room temperature at 80-120 N / cm 2 The pressure is applied for 60 to 120 seconds. Then the pressure can be increased at a temperature between 80°C and 130°C at 100-500 N / cm 2 The hot pressing process is carried out with a pressure of 10000 rpm and the duration is between 60 and 120 seconds.

[0048] At box 440, the soft pack battery can be installed in a clamp press (or some other mechanical device that applies pressure to the soft pack battery). The clamp press can be used to apply prolonged pressure to the SSB soft pack battery. In some embodiments, multiple SSB soft pack batteries are stacked and then compressed using a clamp press. In the clamp press, the SSB soft pack battery may be repeatedly charged and discharged. The SSB soft pack battery can be used to power a vehicle or some other form of electric device.

[0049] As a basis Figure 2 An example of an SSB that can be made according to method 400 can be made, and an SSB soft pack battery including a 16-layer group and having a size of approximately 65mm*65mm can be made. For a given layer, at 0% state of charge (SOC), the thickness is 3.3mm. At 100% SOC, the thickness is 3.64mm, which means that the expansion causes the thickness to increase by about 10%. The performance of the entire battery can be 4520mAh, and the average voltage is 3.79V. At 100% SOC, the energy density (by volume) can be 1122Wh / L; the energy density (by weight) can be 432Wh / Kg.

[0050] The above embodiments focus on the production of a planar layer of a battery cell. Such a layer can be used for a soft-pack battery cell. Figure 5 6, a cylindrical battery cell can be made. Such a cylindrical battery cell can have the same Figure 1 -3, but the manufacturing process of cylindrical battery cells may be different. Figure 5 and Figure 6 to provide further details regarding these embodiments.

[0051] Figure 5An embodiment of a cylindrical battery compression system 500 is illustrated. The cylindrical battery compression system 500 may include: a compression mechanism 510, a heating element 520, a buffer material 530, a cylindrical soft pack battery cell (also referred to as a "battery cell") 540, a temperature sensor 550, a support structure 560, and a platform 570. Embodiments of cylindrical battery compression systems and related systems are described in detail in U.S. Patent Application No. 16 / 412,338, filed on May 14, 2019, entitled "Isostatic Pressing Apparatus and Process for Cylindrical Solid-State Batteries," the entire contents of which are incorporated herein by reference for all purposes. Other embodiments related to systems for isotropically pressurizing cylindrical battery cells are described in detail in U.S. Patent Application No. 16 / 217,010, filed on December 11, 2018, entitled "Hydraulic Isostatic Pressing Process for Solid-State Batteries," the entire contents of which are also incorporated herein by reference for all purposes.

[0052] The shape of the compression mechanism 510 can be approximately cylindrical and have a cross-section similar to a halo. There can be a gap along the curved side wall of the compression mechanism 510. On both sides of this gap are edge 511 and edge 512. By moving edge 511 toward edge 512, the volume inside the compression mechanism 510 can be reduced. Therefore, when edge 511 is away from edge 512, the volume inside the compression mechanism becomes larger, thereby allowing the buffer material and / or battery cell 540 to be installed. When edge 511 is toward edge 512, the volume inside the compression mechanism 510 becomes smaller, thereby applying pressure to the buffer material 530, and applying pressure to the battery cell 540 through the buffer material 530.

[0053] Battery cell 540 may be a cylindrical jelly roll battery cell, such as a Figure 1 -Battery cell of the embodiment of FIG3. The cylindrical jelly roll battery cell may be (initially) stored in a soft bag, which may be compressed using the cylindrical battery compression system 500. After compression and heating using the cylindrical battery compression system 500, the cylindrical jelly roll battery cell may be removed from the soft bag and installed in a cylindrical can, such as detailed in the method 600 of FIG6.

[0054] Compression mechanism 510 can be formed of a semi-rigid material, such as a hard rubber, plastic, or metal layer. Compression mechanism 510 can be partially deformed by edge 511 being pushed or pulled toward edge 512. In some embodiments, edge 512 can be fixed to support structure 560. Edge 511 can be connected to an extension such as a metal rod, which allows a user to manually push or pull the metal rod to move edge 511 toward edge 512. In other embodiments, a hydraulic pump or an electric motor can be used to move edge 511 toward edge 512.

[0055] The buffer material 530 can be wound around the battery cell 540. The buffer material 530 can be a semi-rigid material, such as heat-resistant rubber. In some embodiments, the buffer material 530 can be a rubber or other form of flexible skin filled with liquid. When viewed from a cross section, the buffer material 530 can generally be halo-shaped. This halo shape defines a pore in the center of the buffer material 530, and the battery cell can be placed in the pore. The buffer material 530 can be used to transfer the pressure applied by the compression mechanism 510 to the battery cell 540. The buffer material 530 can help distribute the pressure applied by the compression mechanism 510 so that the pressure applied to the curved side wall of the battery cell 540 is uniform or nearly uniform. In some embodiments, the buffer material 530 is first wound around the battery cell 540. In some embodiments, the buffer material 530 can be a sheet of buffer material in which the battery cell is rolled. Therefore, the jelly roll battery cell can be in the jelly roll of the buffer material. The buffer material 530 can be installed together with the compression mechanism 510.

[0056] Between the buffer material 530 and the compression mechanism 510, there may be a heating element 520. The heating element 520 may be generally cylindrical in shape and may have a gap along the curved sidewall that matches the gap of the compression mechanism 510. The heating element 520 may be a resistive heater so that heat is generated when an electric current is applied to the heating element 520. In some embodiments, the heating element 520 is capable of heating to 250°C. The heat output by the heating element 520 may be controlled based on the output of the temperature sensor 550. The temperature sensor 550 may be located between the battery cell 540 and the buffer material 530. Thus, the temperature sensor 550 may display the temperature at the outer surface of the battery cell 540. In some embodiments, it is preferred to heat the battery cell 540 to between 80°C and 120°C. By applying a higher temperature using the heating element 520, the battery cell 540 may be heated to between 80°C and 120°C faster on its surface. An external heating controller (not shown) may receive temperature measurements from the temperature sensor 550 and control the heat generated by the heating element 520.

[0057] Although edge 512 is fixed to support structure 560, which in turn is fixed to platform 570, edge 511 can remain free. Edge 511 is not constrained by support structure 560 and platform 570, and edge 511 can move toward edge 512, thereby slightly deforming compression mechanism 510. When force is stopped from being applied to edge 511, compression mechanism 510 can expand back to its natural shape, and pressure can be stopped from being applied to battery cell 540. It should be understood that the force applied to edge 511 can be applied near edge 511, without having to be applied precisely on edge 511. However, the closer this force is applied to edge 511, the more evenly the pressure applied to cushioning material 530 can be distributed. Similarly, it should be understood that edge 512 can be fixed directly to support structure 560, but a portion of compression mechanism 510 near edge 512 can be fixed to support structure 560. Here again, the closer the portion of the compression mechanism 510 that is fixed to the support structure 560 is to the edge 512, the more evenly the pressure applied to the cushioning material 530 can be distributed.

[0058] To fabricate a cylindrical battery cell, various methods may be performed. Fig. 6A and Figure 6B An embodiment of a method for making a cylindrical anti-dendrite anode-free solid-state battery is shown. At blocks 605-620, various steps may be performed to make a battery similar to that of reference Figure 1 In other embodiments, blocks 605-620 may be performed to make a reference Figure 2 That is, blocks 605-620 may be performed multiple times for two or more groups (eg, 3-20) of layers.

[0059] Boxes 605-620 represent possible embodiments of how multiple layers are stacked together. In other embodiments, the order of boxes 605-620 may be different. At box 605, the cathode layer may be attached to the cathode current collector layer. The cathode current collector layer may be aluminum foil, and the cathode may be, for example, nickel cobalt alumina (NCA) or nickel manganese cobalt (NCM). The cathode layer may be deposited on the cathode current collector layer, or the cathode current collector layer may be deposited on the cathode layer.

[0060] At box 610, the anti-dendrite layer can be deposited on the anode current collector layer or otherwise attached to the anode current collector layer. The anode current collector layer can be copper, and the anti-dendrite layer can be carbon black, acetylene black, silver, zinc, gold, bismuth, tin, polyvinylidene fluoride (PVDF), polyimide (PI), polyacrylic acid (PAA) and carboxymethyl cellulose butadiene rubber (CMC-SBR). The anti-dendrite layer can also be formed using alloys of silver, zinc, gold, bismuth and tin. The anti-dendrite layer can be used to reduce the nucleation energy of lithium ions to promote the deposition of lithium ions onto the surface of the anode current collector layer.

[0061] At block 615, a dry separator layer, such as dry separator layer 300, can be attached to or otherwise located between a cathode layer or an anti-dendrite layer. The dry separator layer can include two glue layers and a support material, such as described in detail with reference to dry separator layer 300. At block 620, a stack can be made that includes a dry separator layer stacked between a cathode and an anti-dendrite layer. The stack can include at least: a dry separator layer, an anti-dendrite layer, an anode current collector layer, a cathode layer, and a cathode current collector layer, such as Figure 1 As shown (using a dry separator layer instead of the lithium gel separator layer).

[0062] At block 625, the stack may be rolled multiple times to form a jelly roll battery cell. When the layers are rolled together, a generally cylindrical rolled stack may be produced. At block 630, the rolled stack may be inserted into a compressible, flexible soft bag. The soft bag may be a temporary enclosure for a rechargeable battery cell during a portion of the manufacturing process. Prior to sealing the soft bag, an electrolyte solution may be injected or added to the soft bag. The electrolyte solution may be liquid lithium, as described in reference to Figure 3A The injection of liquid lithium may cause the support material of the dry separator layer to be infiltrated by liquid lithium to become a liquid lithium infiltrated support material, such as liquid lithium infiltrated support material 320. As part of block 635, any air present in the soft pack may be removed and the soft pack may be sealed.

[0063] At block 640, pressure may be applied to the soft pack. Pressure may be applied using a system similar to the cylindrical battery compression system 500. Prior to applying pressure, a temperature probe may be inserted so that the temperature probe is adjacent to the outer surface of the soft pack within the cylindrical battery compression system. Pressure may then be applied manually or using a motorized or hydraulic embodiment by the cylindrical battery compression system. The pressure applied may be between 100 kPa and 100 MPa. In some embodiments, the time for applying pressure is between 30 seconds and 1 hour.

[0064] Heat may be applied at box 645, which may be performed simultaneously with box 640 or at least partially overlapped in time with box 640. The applied heat may be between 150°C and 250°C. A temperature probe may be used to monitor the temperature of the soft pack. The heating may be performed until the battery cell is maintained between 60°C and 150°C for a period of time, such as 30 seconds to 1 hour. Pressure, heat, or both may cause the liquid lithium that permeates the support layer to be converted into a quasi-solid lithium gel layer. Therefore, no liquid remains in the soft pack. Therefore, the battery cell is a solid-state battery cell (which includes a gel).

[0065] The heat and pressure applied at blocks 640 and 645 may additionally or alternatively increase the amount of surface area contact between one or more layers of the battery cell. Additionally or alternatively, the heat and pressure may increase adhesion between two or more layers of the battery cell.

[0066] At box 650, the heated and compressed cylindrical jelly roll can be removed from the soft pack. No liquid will appear because it has been transformed into a gel within the support layer. The cylindrical jelly roll can be inserted into a cylindrical battery cell can. The cylindrical battery cell can can be rigid or semi-rigid. In some embodiments, the cylindrical battery cell can can be metal. When the cylindrical jelly roll expands, the cylindrical battery cell can can apply pressure to the cylindrical jelly roll. For example, when the battery cell is charged at box 660, lithium deposition on the anode current collector causes the diameter of the battery to expand by 0.5% to 3%. The pressure applied by the sidewalls of the cylindrical battery cell can can help control the amount of expansion and help keep the layers of the battery cell in contact with each other. At box 660, the battery cell can be repeatedly charged and discharged to power electronic devices such as electric vehicles (EVs). The cylindrical battery manufactured according to method 600 can be charged to 7559Ah and can be discharged to 6229Ah, thus showing an initial coulombic efficiency of 82.4%.

[0067] When lithium is deposited on the anode current collector during charging, it may tend to deposit in a pool rather than in a generally flat film. Because the amount of contact that exists between the deposited lithium and the anode current collector may be small, the electrical connection between the deposited lithium and the anode current collector may be small. Having a small or weak electrical connection between the deposited lithium and the anode current collector can result in a high impedance for the battery cell. High impedance can result in reduced performance of the battery cell: that is, a battery with a low internal resistance may be able to deliver large amounts of current on demand. For certain applications, such as use in electric vehicles (EVs), the ability to deliver current quickly can greatly affect performance, such as the EV's ability to accelerate. When a battery cell has a high internal resistance, the current flowing through the battery cell can cause the battery to heat up, which can damage the battery cell.

[0068] In some embodiments, an additional layer may be present in the stack of anode-free solid-state batteries. The additional layer may be located between the anti-dendrite layer and the anode current collector. This layer may be referred to as an interfacial bonding layer. The interfacial bonding layer may promote the formation of lithium deposits with a high degree of surface contact between the interfacial bonding layer and the lithium deposits. Since the interfacial bonding layer has a large amount of contact with both the anode current collector and the deposited lithium, the internal resistance of the battery cell may be reduced. Such an interfacial bonding layer may be added to the reference Figure 1 -6 or reference Figure 7-10 In any of the embodiments described in detail.

[0069] The interface layer may be made of a conductive agent and a binder. In some embodiments, the interface layer may be between 30%-99% conductive agent; the remainder of the interface bonding layer may be a binder (1%-70%). Figure 7 An embodiment of a stack 700 of an anode-free solid-state battery having a lithium gel separator layer, an anti-dendrite layer, and an interfacial bonding layer is shown. Figure 1 The stack 700 is described in detail. However, an interfacial bonding layer 710 may be present between the anode current collector 150 and the anti-dendrite layer 140. The interfacial bonding layer 710 may be in direct contact with the anti-dendrite layer 140 on a first side and in direct contact with the anode current collector 150 on an opposite second side.

[0070] In order to promote the deposition of lithium metal on the interfacial bonding layer 710, the first adhesion amount of the interfacial bonding layer 710 to the anode current collector 150 may be greater than the second adhesion amount between the anti-dendrite layer 140 and the interfacial bonding layer 710 or the third adhesion amount between the anti-dendrite layer 140 and the lithium gel separator layer 130. The thickness of the interfacial bonding layer 710 may be between 0.05 μm and 5 μm. The density of the interfacial bonding layer may be between 0.1 g / cm 3 Up to 2.0g / cm 3 between.

[0071] The interface bonding layer 710 can use carbon as a conductive agent mixed with a binder (PvDF, SBR-CMC, PAA) and metal particles such as Bi, Sn, Ag, Au, Pt. More specifically, acetylene black or carbon black can be used as a conductive agent. A single carbon particle can be a spherical particle between 3nm and 20nm. Possible binder types include: PvDF, SBR-CMC and PAA.

[0072] With such as Figure 1 Compared with the embodiment (wherein the interface bonding layer 710 is not present), Figure 7 The impedance or resistance of the battery cell (as measured between terminal 720 and terminal 730) may be significantly reduced due to the presence of the interfacial bonding layer 710. For example, an embodiment of a battery cell without an interfacial bonding layer may have an impedance of 0.85Ω; but if an interfacial bonding layer is present between the anode current collector and the anti-dendrite layer, the impedance may be 0.05Ω.

[0073] Figure 8 An embodiment of a stack 800 of a solid-state battery without an anode is shown indicating the relative amounts of adhesion between the various layers. Figure 7 An important aspect of the stack 700 may be the relative amount of adhesion between the layers to facilitate the plating of lithium metal between the anti-dendritic layer 140 and the interfacial bonding layer 710 during charging.

[0074] The interface 801 between the lithium gel separator layer 130 and the anti-dendrite layer 140 may have a first adhesion amount. The interface 802 between the anti-dendrite layer 140 and the interfacial bonding layer 710 may have a second adhesion amount. The interface 803 between the interfacial bonding layer 710 and the anode current collector 150 may have a third adhesion amount. By making the interface 802 have less adhesion than the interface 801 or the interface 803, lithium plating at the interface 802 may be promoted. In other words, the second adhesion amount may be greater than the first adhesion amount or the third adhesion amount.

[0075] Fig. 9 An embodiment 900 of a stack of anode-free solid-state batteries is shown in which lithium ions migrate and deposit onto an interfacial bonding layer. In embodiment 900, the battery cell is being charged. Charging causes lithium ions to migrate from the cathode 120, through the lithium gel separator layer 130, through the anti-dendrite layer 140, and plate into a lithium metal layer 910 between the anti-dendrite layer 140 and the interfacial bonding layer 710, as shown by arrow 905. The anti-dendrite layer 140 can help inhibit the growth of dendrites that may pierce the lithium gel separator layer 130. Therefore, the interfacial bonding layer 710 can be used in combination with the anti-dendrite layer 140.

[0076] The presence of the lithium metal layer 910 may cause the battery cell to swell. During a discharge cycle, lithium ions may migrate from the lithium metal layer 910 to the cathode 120. As the battery cell discharges and the lithium ions migrate to the cathode layer 120, the swelling within the battery cell may be reduced.

[0077] Fig.10 An embodiment of a method 1000 for making a pouch cell comprising an anode-free solid-state battery having a lithium gel separator layer, an anti-dendrite layer, and an interfacial bonding layer is shown. It should be understood that the method 1000 may be based on Fig. 6A and Figure 6B The blocks of method 600 are modified so that the interfacial bonding layer can be fabricated as part of a cylindrical battery cell.

[0078] At block 1005, an interfacial bonding layer may be deposited onto the anode current collector. Figure 1 The anode current collector 150 is described in detail. Block 1005 may include a conductive material, such as acetylene black, mixed with a binder and deposited on the anode current collector.

[0079] At block 1010, a three-part lithium gel separator layer may be formed. Initially, the lithium gel separator layer may be in the form of a dry separator layer. That is, a liquid electrolyte, such as liquid lithium, has not yet been infused or infiltrated throughout the support layer, as described in reference to FIG. Figure 3AIn other embodiments, the scaffold material has been infiltrated with a liquid. At block 1020, an anti-dendrite layer may be laminated to the lithium gel separator layer, where liquid lithium (or another liquid electrolyte) may or may not have been introduced. Figure 1 The anti-dendrite layer 140 is described in detail. In some cases, the adhesion between the lithium gel separator layer and the anti-dendrite layer can be greater than the adhesion between the anti-dendrite layer and the interface bonding layer.

[0080] At block 1025, the cathode layer can be laminated onto the lithium gel separator layer (where the gel is still in liquid form or not yet present). At block 1030, the cathode current collector layer can be laminated onto the cathode layer. In some embodiments, block 1030 can be performed and then the combined cathode and cathode current collector layer can be laminated onto the lithium gel separator layer at block 1025.

[0081] At box 1032, the anti-dendrite layer previously stacked on the lithium gel separator layer can have its opposite side layer stacked on the interfacial bonding layer. The stacking of the anti-dendrite layer and the interfacial bonding layer may result in relatively small adhesion between the layers. The anti-dendrite layer can form an interface, and the adhesion between the interface and the interfacial bonding layer is smaller than the adhesion between the anode current collector and the interfacial bonding layer. The adhesion amount can be controlled by adjusting the ratio of the binder and the active conductive material of the interfacial bonding layer. For example, PvDF can be used as a binder and Ketjen black can be used as an active material, with a ratio of 3% PvDF to 97% Ketjen black. In other embodiments, the proportion of Ketjen black is between 95% and 98%.

[0082] It should be understood that blocks 1005-1030 may be repeated multiple times to form multiple stacks for a solid-state battery cell. Figure 2 16 layers were made in the stack described, plus an interfacial bonding layer. This arrangement allowed the anode current collector and cathode current collector to contact the anti-dendrite layer and cathode, respectively, on opposite sides.

[0083] At box 1035, one or more stacks may be packaged in a soft pack battery. At this box, the liquid lithium (or other form of liquid electrolyte), assuming it was introduced at box 1015, may still be liquid. The stack can be vacuum sealed within the soft pack battery to remove excess air. The soft pack battery can be made of a flexible material, such as plastic, which can expand and compress the soft pack. If the liquid electrolyte (e.g., liquid lithium) does not penetrate the entire support layer at box 1015, the liquid electrolyte can be introduced into the soft pack battery at box 1040 while packaging is being performed (or before or after). The liquid lithium can then penetrate into the support layer of the dry separator layer.

[0084] At box 1045, one or more processes of heating, pressurizing, or both may be applied to the packaged soft pack battery. This process may perform multiple functions: 1) box 1045 may increase the amount of physical contact between adjacent layers of the battery cell; 2) box 1045 may convert the liquid electrolyte (e.g., liquid lithium) into lithium gel; and 3) box 1045 may help generate an adhesion between the interfacial bonding layer and the anode current collector that is greater than the adhesion between the anti-dendrite layer and the interfacial bonding layer. For example, in some embodiments, the first step may be to heat the anode current collector at room temperature at 80-120 N / cm 2 Pressure is applied and held for 60 to 120 seconds. This part of the process can increase the amount of contact that exists at one of the multiple interfaces of the layers of the battery cell. Pressure can then be applied at 100-1000 N / cm at a temperature between 50°C–130°C. 2 The hot pressing process is carried out at a pressure of 10000 s and the duration is between 60 and 2400 seconds.

[0085] At box 1050, the soft pack battery can be installed in a clamp press (or some other mechanical device that applies pressure to the soft pack battery). The clamp press can be used to apply pressure to the SSB soft pack battery for a long time. In some embodiments, multiple SSB soft pack batteries are stacked and then compressed using a clamp press. In the clamp press, the SSB soft pack battery may be repeatedly charged and discharged. The SSB soft pack battery can be used to power a vehicle or some other form of electric device.

[0086] The methods, systems, and devices discussed above are examples. Various configurations may omit, replace, or add various processes or components as appropriate. For example, in alternative configurations, the method may be implemented in an order different from the order described, and / or various stages may be added, omitted, and / or combined. Moreover, features described with respect to certain configurations may be combined in various other configurations. Different aspects and elements of the configurations may be combined in a similar manner. Moreover, technology is evolving, and thus, many of the elements are examples and do not limit the scope of the present disclosure or claims.

[0087] Specific details are given in the specification to provide a thorough understanding of example configurations (including implementations). However, configurations can be practiced without these specific details. For example, in order to avoid confusing configurations, well-known processes, structures, and techniques have been shown without unnecessary details. This description only provides example configurations and does not limit the scope, applicability, or configuration of the claims. On the contrary, the previous description of the configuration will provide a description of the enabling technology for implementing the described technology to those skilled in the art. Various changes may be made to the functions and arrangements of the elements without departing from the spirit or scope of the present disclosure.

[0088] In addition, a configuration may be described as a process, which is depicted as a flow chart or block diagram. Although each operation may be described as a sequential process, many operations may be performed in parallel or simultaneously. In addition, the order of the operations may be rearranged. A process may have other steps not included in the figure.

[0089] Several example configurations have been described, and various modifications, alternative constructions, and equivalents may be employed without departing from the spirit of the present disclosure. For example, the above elements may be components of a larger system, in which other rules may take precedence over the present invention or otherwise modify the application of the present invention. Likewise, many steps may be taken before, during, or after considering the above elements.

Claims

1. A phase change electrolyte for a solid state battery (SSB), the phase change electrolyte comprising a phase change electrolyte separator layer, the phase change electrolyte separator layer comprising a non-reactive support and a lithium gel, wherein the physical structure of the non-reactive support forms an open space within the non-reactive support; The lithium gel is formed by a liquid electrolyte mixture filled into the open space and includes a polymer additive, a cross-linking agent additive, a lithium salt, and a solvent that dissolves the lithium salt, wherein: The polymer additive includes poly-4-vinylpyridine (P4VP); The crosslinker additive is selected from the group consisting of: N,N,N',N'-tetrakis(trifluoromethanesulfonyl)-dodecane-1,12-diamine (C12TFSA), N,N,N',N'-tetrakis(trifluoromethanesulfonyl)-hexane-1,6-diamine (C6TFSA) and any combination thereof; wherein the phase-change electrolyte separator layer further comprises a first glue layer and a second glue layer, wherein the first glue layer contacts the non-reactive support on a first side, and the second glue layer contacts the non-reactive support on a second side; wherein the phase change electrolyte diaphragm layer further comprises an anti-dendritic layer in contact with the first glue layer or the second glue layer; and The phase change electrolyte separator layer further comprises an interface bonding layer in direct contact with the anode current collector of the solid-state battery (SSB), the interface bonding layer is located between the anti-dendritic layer and the anode current collector, the interface bonding layer is made of a conductive agent and a bonding material, wherein the conductive agent comprises carbon, the bonding material comprises polyvinylidene fluoride (PvDF), styrene-butadiene rubber / sodium carboxymethyl cellulose (SBR / CMC) or polyacrylic acid (PAA), and the density of the interface bonding layer is 0.1 g / cm 3 To 2.0g / cm 3 between.

2. The phase-change electrolyte for solid-state batteries according to claim 1, wherein the non-reactive support is composed of polyethylene (PE) or polyethylene oxide (PEO).

3. The phase change electrolyte for a solid-state battery according to claim 1, wherein the lithium salt is selected from the group consisting of: LIFSI, LITFSI and LiPF6. 4 . The phase-change electrolyte for a solid-state battery according to claim 1 , wherein the first glue layer and the second glue layer comprise ceramics.

5. The phase change electrolyte for solid-state batteries according to claim 1, characterized in that: The anti-dendrite layer includes at least one of silver, zinc, gold, bismuth, tin or alloys thereof.

6. The phase change electrolyte for solid-state batteries according to claim 1, characterized in that: The conductive agent is carbon black.

7. The phase change electrolyte for solid-state batteries according to claim 1, characterized in that: The conductive agent is acetylene black.

8. The phase change electrolyte for solid-state batteries according to claim 1, characterized in that: Based on the weight of the interface bonding layer, the conductive agent is 30% to 99%, and the bonding agent material is 1% to 70%.

9. A method for preparing a phase change electrolyte for a solid-state battery (SSB), the method comprising: The interface bonding layer is deposited on the anode current collector, wherein the interface bonding layer is made of a conductive agent and a bonding material, the conductive agent includes carbon, the bonding material includes polyvinylidene fluoride (PvDF), styrene butadiene rubber / sodium carboxymethyl cellulose (SBR / CMC) or polyacrylic acid (PAA), and the density of the interface bonding layer is 0.1 g / cm 3 to 2.0 g / cm 3 between; Forming a lithium gel separator layer, wherein forming the lithium gel separator layer comprises: forming a non-reactive scaffold such that the physical structure of the non-reactive scaffold forms open spaces within the non-reactive scaffold; forming a liquid electrolyte mixture, the liquid electrolyte mixture comprising a polymer additive, a crosslinker additive, a lithium salt, and a solvent for dissolving the lithium salt, wherein the polymer additive comprises poly-4-vinylpyridine (P4VP), and the crosslinker additive is selected from the group consisting of: N,N,N',N'-tetrakis(trifluoromethanesulfonyl)-dodecane-1,12-diamine (C12TFSA), N,N,N',N'-tetrakis(trifluoromethanesulfonyl)-hexane-1,6-diamine (C6TFSA), and any combination thereof; infiltrating the liquid electrolyte mixture into the open spaces within the non-reactive support; and After the liquid electrolyte mixture has infiltrated into the open spaces within the non-reactive support, heating the liquid electrolyte mixture to convert the liquid electrolyte mixture into a lithium gel electrolyte within the non-reactive support; laminating an anti-dendrite layer onto the lithium gel separator layer; and An anti-dendrite layer is laminated on the interfacial bonding layer.

10. The method for manufacturing a phase change electrolyte for a solid-state battery according to claim 9, further comprising: Prior to infiltrating the liquid electrolyte mixture into the open spaces within the non-reactive support, a first glue layer is attached to a first side of the non-reactive support.

11. The method for manufacturing a phase change electrolyte for a solid-state battery according to claim 10, further comprising: Prior to infiltrating the liquid electrolyte mixture into the open space within the non-reactive support, a second glue layer is attached to a second side of the non-reactive support opposite the first side of the non-reactive support.

12. The method for manufacturing a phase change electrolyte for a solid-state battery according to claim 11, further comprising: The non-reactive support to which the first glue layer and the second glue layer are attached is stacked between the cathode layer and the anti-dendrite layer.

13. A method for making a phase change electrolyte for a solid-state battery as described in claim 12, wherein stacking the non-reactive support to which the first adhesive layer and the second adhesive layer are attached between the cathode layer and the anti-dendrite layer occurs before infiltrating the liquid electrolyte mixture into the open space within the non-reactive support. 14 . The method for manufacturing a phase change electrolyte for a solid-state battery according to claim 13 , wherein the first glue layer and the second glue layer comprise ceramics.

15. The method for manufacturing a phase-change electrolyte for a solid-state battery according to claim 9, wherein the non-reactive support is composed of polyethylene (PE) or polyethylene oxide (PEO).

16. The method for manufacturing a phase change electrolyte for a solid-state battery according to claim 9, wherein the lithium salt is selected from the group consisting of: LIFSI, LITFSI and LiPF6.

17. A solid-state battery (SSB), comprising a cathode, an anode current collector, and a phase-change electrolyte separator layer between the cathode and the anode current collector, the phase-change electrolyte separator layer comprising a non-reactive scaffold and a lithium gel, wherein the physical structure of the non-reactive scaffold forms an open space within the non-reactive scaffold, the lithium gel is formed by a liquid electrolyte mixture filled into the open space and comprises a polymer additive, a cross-linker additive, a lithium salt, and a solvent for dissolving the lithium salt, wherein: The polymer additive includes poly-4-vinylpyridine (P4VP); The crosslinking agent additive is selected from the group consisting of: N,N,N',N'-tetrakis(trifluoromethanesulfonyl)-dodecane-1,12-diamine (C12TFSA), N,N,N',N'-tetrakis(trifluoromethanesulfonyl)-hexane-1,6-diamine (C6TFSA) and any combination thereof; The phase-change electrolyte separator layer further comprises a first glue layer and a second glue layer, wherein the first glue layer contacts the non-reactive support on a first side, and the second glue layer contacts the non-reactive support on a second side; The phase change electrolyte diaphragm layer further includes an anti-dendritic layer in contact with the first glue layer or the second glue layer; and The phase change electrolyte separator layer further comprises an interface bonding layer in direct contact with the anode current collector of the solid-state battery (SSB), the interface bonding layer is located between the anti-dendritic layer and the anode current collector, the interface bonding layer is made of a conductive agent and a bonding material, wherein the conductive agent comprises carbon, the bonding material comprises polyvinylidene fluoride (PvDF), styrene-butadiene rubber / sodium carboxymethyl cellulose (SBR / CMC) or polyacrylic acid (PAA), and the density of the interface bonding layer is 0.1 g / cm 3 To 2.0g / cm 3 between.

18. The solid-state battery according to claim 17, characterized in that: The anti-dendrite layer includes at least one of silver, zinc, gold, bismuth, tin or alloys thereof.

19. The solid-state battery according to claim 17, characterized in that: The conductive agent is carbon black.

20. The solid-state battery according to claim 17, characterized in that: The conductive agent is acetylene black.

21. The solid-state battery according to claim 17, characterized in that Based on the weight of the interface bonding layer, the conductive agent is 30% to 99%, and the bonding agent material is 1% to 70%.

Citation Information

Patent Citations

  • Hydraulic isostatic press processes for solid-state batteries

    US10403925B1

  • Isostatic press devices and processes for cylindrical solid-state batteries

    US10957935B2

  • Secondary battery

    US20160087305A1

  • Secondary battery

    US20170179520A1

  • Lithium secondary battery

    US5538814A